Azotochelin and N-dihydroxy-N,N’-diisopropylhexanediamide as Fe sources to cucumber plants in hydroponic cultures - Martins, Joao Graca; Apaolaza, Clara Martin, Lourdes; Barros, Maria Teresa; Soares, Helena Maria Vieira Monteiro; Lucena, Juan Jose (Emirates Journal of Food and Agriculture, 2018)
Environmental concerns related to the use of synthetic iron chelates, usually non-biodegradable, for overcoming iron chlorosis motivates the search for alternative compounds. Thus, the main aim of this work was to evaluate siderophore, azotochelin, and a siderophore mimic, N-dihydroxy-N,N’-diisopropylhexanediamide (DPH) as potential sources of iron to cucumber plants grown in hydroponic cultures. The behavior of the iron chelates of azotochelin and DPH, as a substrate of ferric chelate reductase (FCR) and the ability as iron suppliers for chlorotic plants was studied and compared with o,o-EDDHA/Fe3+ and EDTA/Fe3+ chelates, traditionally used for this purpose. The rate of reduction of DPH/Fe3+, by FCR, was comparable to o,o-EDDHA/Fe3+ but lesser than the obtained for EDTA/Fe+3. The rate of reduction for azotochelin/Fe3+ was not possible to determine. Both azotochelin/Fe3+ and DPH/Fe3+ chelates were effective in supplying iron to cucumber plants. After 7 and 21 days, all the plants treated with the iron chelates (10 µM, Fe) of DPH and azotochelin showed significantly higher SPAD index, leaf dry weight and leaf Fe concentration than the control plants (2µM, Fe). In conclusion, azotochelin/Fe3+ and DPH/Fe3+ can be considered as iron sources for cucumber plants when growing in hydroponic culture.